(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the advantages and effectiveness of using gamification technologies in teaching Algebra and Fundamentals of Mathematical Analysis in academic lyceums. Gamification contributes to enhancing students’ motivation, making the learning process more engaging, and facilitating the comprehension of complex mathematical concepts. The study examines the impact of interactive game-based platforms, point systems, leaderboards, and reward mechanisms on the educational process. The findings indicate that gamification plays a significant role in increasing student engagement and strengthening knowledge acquisition.